Crop Management Practices and Labor Inputs for Hop Production in Florida - Shinsuke Agehara; Mariel Gallardo; Aleyda Acosta-Rangel; Zhanao Deng; Jack Rechcigl; Tianyuan Luo; Qi Qiu (EDIS)
The booming craft beer industry, rising prices of hops, and demand for locally-produced ingredients have recently increased interest in local hop production among growers and brewers. This article describes crop management practices and labor inputs required for small-scale hop production in Florida, with the aim of assisting growers with investment and farm management decisions. It is part of a larger series that will review the challenges of hop production in Florida, based on research experience at the UF/IFAS Gulf Coast Research and Education Center in Balm, FL. This new 6-page publication of the UF/IFAS Horticultural Sciences Department was written by Shinsuke Agehara, Mariel Gallardo, Aleyda Acosta-Rangel, Zhanao Deng, Jack Rechcigl, Tianyuan Luo, and Qi Qiu. https://edis.ifas.ufl.edu/hs1409